Experimental analysis of the universal continuous digging machine working processes - Gerlici, Juraj; Musiiko, Volodymyr; Koval, Andrii; Nikolaenko, Volodymyr; Lazaruk, Jurii; Lack, Tomas; Kravchenko, Kateryna (Manufacturing Technology Journal, 2020)
The article presents the results of experimental research on creating the mobile continuous earthmoving machin-ery. Methods for performing field experimental studies and measuring equipment used are described. The article shows the data of experimental research, their analysis, the determination of physical nature of changes in exter-nal load characteristics of the machinery operating equipment. The conducted experimental studies of modern mobile earthmoving machinery enabled to establish its technical capabilities, the characteristics of the power load of the operating equipment when developing the soil. It also enabled to determine the ways and directions for mod-ernizing the operating equipment of machinery. One of the ways is to optimize technological combination of soil cutting, displacement of the developed soil to the unloading area and unloading of the actuator. The research per-formed and the results obtained have enabled to experimentally confirm the effectiveness of the technical pro-posals to create the design of the chain and bar actuators with impulse soil unloading intensifiers for trenchers implemented in the industry.
Keywords: Tensometric System; Recording Equipment; Torque and Driveshaft Rotation Speed Sensor; Hydraulic Fluid Pressure Sensor